Absolute music and the construction of meaning - Chua, Daniel K. L. (Cambridge Cambridge University Press, 1999)
This book examines the intellectual history of instrumental music, in particular the idea of absolute music. It tries to show how certain ideas in philosophy, theology and the sciences affect the meaning and, indeed, the existence of instrumental music, and how, in turn, instrumental music is used to resolve or exemplify certain problems in modern culture. Instead of existing in a pure and autonomous form, music is woven back into the epistemological fabric and entangled with numerous discourses, thus demonstrating the centrality of music in the construction of meaning.